2023
DOI: 10.34172/jhp.2023.43
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of water lily (Nymphaea pubescens Willd) seed ethanolic extract against trimethyltin-induced cognitive impairment and neurodegeneration in mice

Dinda Fadhilah Belahusna,
Putra Santoso,
Resti Rahayu

Abstract: Introduction: Cognitive impairments are profound outcomes of neurodegenerative disease, a global health issue. Water lily (Nymphaea pubescens, Nymphaeaceae) extracts have been reported to counteract oxidative stress. However, their protective effects against neurodegenerative disease remain to be fully investigated. The current study aimed to determine the neuroprotective effect of water lily seed ethanolic extract on trimethyltin (TMT)-induced cognitive impairment and neurodegeneration in a mouse model. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…1 Nowadays, people turn to herbal medicine because they believe that plant remedies are relatively safe than synthetic medicine. 2 Reports have shown that food consumption may modulate and activate immune function and response. Consumption of rambutan fruit in the community left waste in the form of rambutan peel.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nowadays, people turn to herbal medicine because they believe that plant remedies are relatively safe than synthetic medicine. 2 Reports have shown that food consumption may modulate and activate immune function and response. Consumption of rambutan fruit in the community left waste in the form of rambutan peel.…”
Section: Introductionmentioning
confidence: 99%